THE IMPACT OF DIGITAL PLATFORMS ON INTERNATIONAL TOURISM COOPERATION: EVIDENCE FROM UZBEKISTAN AND CENTRAL ASIA - Jumanova Ranokhon Anvar qizi (International Journal of Literature and Language Studies, 2026)
The digital revolution has transformed the tourism industry by reshaping how destinations are promoted, how tourists access information, and how tourism stakeholders cooperate across borders. In recent years, digital platforms have emerged as key drivers of international tourism cooperation, enabling countries to improve destination visibility, facilitate service integration, and strengthen regional partnerships. This study examines the impact of digital platforms on international tourism cooperation in Uzbekistan and Central Asia. Using a qualitative research approach based on secondary data analysis, the study evaluates how digital technologies contribute to tourism growth, regional integration, and cross-border collaboration. The findings reveal that digital platforms significantly enhance tourism competitiveness through online marketing, e-visa systems, digital payment technologies, smart tourism applications, and social media engagement. The study further demonstrates that regional cooperation supported by digital technologies can increase tourist flows, improve service quality, and strengthen Central Asia's position in the global tourism market.